Outcome of Elderly Patients With Surgically Treated Brain Metastases - Heimann, Muriel; Schäfer, Niklas; Bode, Christian; Borger, Valeri; Eichhorn, Lars; Giordano, Frank A.; Güresir, Erdem; Jacobs, Andreas H.; Ko, Yon-Dschun; Landsberg, Jennifer; Lehmann, Felix; Radbruch, Alexander; et al. (Frontiers in Oncology, 2021)
Object: In the light of an aging population and ongoing advances in cancer control, the optimal management in geriatric patients with brain metastases (BM) poses an increasing challenge, especially due to the scarce data available. We therefore analyzed our institutional data with regard to factors influencing overall survival (OS) in geriatric patients with BM. Methods: Between 2013 and 2018, patients aged ≥ 65 years with surgically treated BM were included in this retrospective analysis. In search of preoperatively identifiable risk factors for poor OS, in addition to the underlying cancer, the preoperative frailty of patients was analyzed using the modified Frailty Index (mFI). Results: A total of 180 geriatric patients with surgically treated BM were identified. Geriatric patients categorized as least-frail achieved a median OS of 18 months, whereas frailest patients achieved an OS of only 3 months (p<0.0001). Multivariable cox regression analysis detected "multiple intracranial metastases" (p=0.001), "infratentorial localization" (p=0.011), "preoperative CRP >5 mg/l" (p=0.01) and "frailest patients (mFI ≥ 0.27)" (p=0.002) as predictors for reduced OS in older patients undergoing surgical treatment for BM. Conclusions: In this retrospective series, pre-operative frailty was associated with poor survival in elderly patients with BM requiring surgery. Our analyses warrant thorough counselling and support of affected elderly patients and their families.